Otimização da logística reversa de medicamentos de uso humano vencidos e/ou em desuso no município de Fortaleza-CE. - Feitosa, Alexandra de Vasconcelos (2016)
The monitoring of residual drugs in the environment is gaining great interest due to the fact that these substances are frequently found in different environmental matrices. The ease of acquiring medicines, the lack of information about the damages caused and the lack of points of collection of medicines proves the need to promote measures that seek to alleviate the problems related to the incorrect disposal of medicines for home use. One of these measures is the implementation of reverse logistics systems for medicines, by returning products after use by the consumer. These measures are recommended in the State Solid Waste Policy of the State of Ceará and through Laws 15,192 and 9,927, both of 2016. The present work aimed to analyze the reverse logistics of medicines through the use of semi-structured questionnaires for Authors involved in the process and optimize the reverse logistics logistics process by developing a methodology for allocating drug collection points in the city of Fortaleza-CE using linear programming. The results indicate that the reverse logistics process occurs between the pharmaceutical industry, the distributors and the pharmacies, and the process is inefficient between the final consumer and the pharmacy. The study showed that the most common form of medication disposal by the population is the common waste (84.7%) and 0.5% of the population interviewed returns the leftovers from the medicines to the pharmacies. Regarding environmental awareness, 48.6% of the population and 88.9% of the pharmacists interviewed believe that the incorrect disposal of medication causes environmental problems. Most of the pharmacies visited (97.2%) do not have a program to collect overdue drugs and surpluses, even with specific legislation in the state and municipality. Through statistical and mathematical modeling it was possible to develop a methodology that suggested 52 collection points would be necessary to meet the initial demand of the population of the city of Fortaleza-CE for the collection of medicines.